Antitumour effects of Morinda citrifolia L. fruit and Clinacanthus nutans (Burm. F.) lindau leaf mixtures in leukaemia- lymphoma bearing Sprague Dawley rats - Mohamad Iffendi, Sajjarattul Nurul Nadia Asyura (2016)
Morinda citrifolia L. (M. citrifolia) fruit known as ‘mengkudu’ and Clinacanthus nutans (Burm. F.) Lindau (C. nutans) leaf known as ‘rumput belalai gajah’, are widely known herbs that have anti-cancer properties. The antitumour effects of the combination of these herbs in leukaemia-lymphoma have never been reported. The aim of this study were to evaluate toxicity of ethanol extracts of M. citrifolia fruits and C. nutans leaves and the antitumour effects of these ethanol extracts in MNU-induced leukaemia-lymphoma. The antitumour of MNU-induced leukaemia-lymphoma rats was evaluated via haematological and serum biochemical parameters, histopathology, levels of an oxidative stress biomarker (malondialdehyde [MDA]) and antioxidative stress enzymes (glutathione peroxidase [GPx] and superoxide dismutase [SOD], transcription levels of VEGF and COX-2 mRNA in the blood, spleen and lymph nodes and expression levels of VEGF and COX-2 protein in the spleen and lymph nodes. A 14-day acute toxicity was conducted for determination of lethal dose 50 (LD50), followed by a 28-day subacute toxicity study and a 13-week subchronic toxicity study of both extracts. In acute toxicity, rats were divided into four groups, namely, control, 10% DMSO (vehicle) and 2000 mg/kg of body weight of each extract. In the subacute and subchronic toxicities, rats were divided into eight groups including control, 10% DMSO (vehicle), 75 mg/kg body weight, 125 mg/kg body weight and 250 mg/kg body weight of each extract. At the end of the experimental period, blood samples were collected for the hematological and serum biochemical parameters. The liver and kidneys were collected for histopathological analysis. The results showed a single dose (2000 mg/kg of body weight) of ethanol extracts of M. citrifolia fruits and C. nutans leaf induced no acute toxicity to the male Sprague Dawley rats. The oral administration of 75 mg/kg of M. citrifolia fruit and C. nutans leaf for 28 and 90 days induced no subacute and subchronic toxicity in male Sprague Dawley rats. Administration of 125 mg/kg of M. citrifolia fruit and C. nutans leaf for 28 and 90 days induced hepatotoxicity in male Sprague Dawley rats. Administration of 250 mg/kg of M. citrifolia fruit and C. nutans leaf for 28 and 90 days induced hepatotoxicity and nephrotoxicity in male Sprague Dawley rats. In the MNU-induced leukaemia-lymphoma study, a total of 56 rats were divided into seven groups namely control (group A), MNU-induced leukaemia-lymphoma rats (group B), MNU-induced leukaemia-lymphoma rats treated with four different combinations of M. citrifolia and C. nutans extracts (mixture C [group C], mixture D [group D], mixture E [group E] and mixture F [group F]) and MNU-induced leukaemia-lymphoma rats treated with chemotherapy regimen (CHOP) (group G). Leukaemia-lymphoma was induced using N-methyl-N-nitrosourea (MNU) which was administered intraperitoneally (i.p) at a dose of 60 mg/kg of body weight for four times in the 2-week period. Mixtures of herbs for treatment of the leukaemia-lymphoma rats were formulated not to exceed 250 mg/kg of body weight per administration. The herbal mixed extracts were given via oral gavage, once daily starting from week 12 post MNU administration until week 24 of the experiment period. Blood samples were collected and analysed on the 18th and 24th weeks of the experiment. Heart, lungs, liver kidneys, lymph nodes and spleen were collected for histopathological evaluation. The results showed the presence of blast cells in the blood smear in both untreated and treated leukaemia-lymphoma rats at week 18th and 24th. Groups B and G had a significant elevation in the number of blast cells from week 18 to week 24. The oral administration of herbal mixtures (groups C, D, E and F) was effective in limiting the degree of leukaemic cells progression. The serum biochemical parameter results showed CK level was significantly increased in groups C, D and F from week 18 to week 24. The LDH level had also significantly increased in groups C and F from week 18 to week 24. Histopathology results showed neoplastic lymphocytes were present in all spleen and lymph nodes of the untreated and treated MNU-induced leukaemia-lymphoma rats. The oral administration of mixtures E and F in MNU-induced leukaemia-lymphoma rats inhibited metastasise of neoplastic lymphocytes to the selected vital organs (liver, lungs, heart and kidneys) as compared to other herbal mixtures and CHOP regimen. Treatment of CHOP regimen in MNU-induced leukaemia-lymphoma rats induced significant liver and spleen fibrosis and necrosis in the testis. However, treatment of herbal mixtures in MNU-induced leukaemia-lymphoma rats induced no fibrosis and necrosis (testis). The levels of serum MDA in the MNU-induced leukaemia-lymphoma rats treated with all herbal mixtures and CHOP regimen were decreased from week 18 to week 24. The level of serum SOD in MNU-induced leukaemia-lymphoma rats treated with herbal mixtures and CHOP regimen increased from week 18 to week 24. A decrease of serum GPx was observed from week 18 to week 24 in all groups. Administration of MNU-induced leukaemia-lymphoma rats with herbal mixtures succeeded in inhibiting angiogenesis and inflammation in blood, lymph node and spleen compared to untreated MNU-induced leukaemia-lymphoma rats. A down-regulated of VEGF and COX-2 mRNA transcription was observed especially in MNU-induced leukeamia-lymphoma rats treated with mixtures E and F compared to untreated MNU-induced leukeamia-lymphoma. On the other hand, treatment of mixture F succeeded to inhibit COX-2 expression in the lymph nodes of MNU-induced leukaemia-lymphoma rats via immunohistochemistry. A more sensitive result was obtained from Western blot whereby mixtures E and F were able to decrease VEGF and COX-2 expression in MNU-induced leukeamia-lymphoma rats. In conclusion, oral administration of 2000 mg/kg of body weight of both extracts in male Sprague Dawley rats induced no acute toxicity. Oral administration of 125 mg/kg of body weight for 29 and 90 days of both extracts induced hepatotoxicity. Oral administration of 250 mg/kg of body weight for 29 and 90 days of both extracts induced hepatotoxicity and nephrotoxicity. Oral administration of herbal extracts (group C, D, E and F) limited leukaemic cell progression in MNU-induced leukaemia-lymphoma rats. Oral administration of mixtures E and F inhibited the metastasise of neoplastic lymphocytes in heart, lungs, liver and kidneys. Oral administration of all herbal mixtures down-regulated the serum MDA level in the MNU-induced leukaemia-lymphoma rats. It also enhanced the production of serum SOD level in the MNU-induced leukaemia-lymphoma rats treated with all herbal mixtures. Oral administration of mixtures E and F was able to down-regulate VEGF and COX-2 transcription and expression in MNU-leukaemia-lymphoma rats.